Stratum corneum cytokine levels in mycosis fungoides. Issue 2 (10th November 2022) - Nguyen, Anh Ly; Kezic, Sanja; Vermeer, Maarten; Quint, Koen; Slieker, Roderick; van Doorn, Remco; Rustemeyer, Thomas
Abstract: Mycosis fungoides (MF) is characterised by malignant CD4 + T‐cell infiltrates in the skin. The functional characteristics of the malignant T cells and their interaction with the tumor immune microenvironment is largely unknown. We performed tape stripping of the stratum corneum (SC), a non‐invasive technique, to gain insight into the cytokine secretion patterns in MF skin lesions. In addition, we assessed whether the SC cytokine profile of MF lesions is distinct from that of atopic dermatitis (AD) lesions. We compared nine cytokine levels in 20 patients with MF, 10 patients with AD and 10 healthy controls. In patients with MF and AD, lesional SC levels of IL‐8 and MMP9 were significantly higher than in non‐lesional SC and in healthy controls. VEGFα was significantly higher in lesional MF and AD skin than in healthy controls. The SC levels of IL‐1α were significantly lower in MF and AD lesions than in healthy controls. There was no specific cytokine profile or inflammation pattern that could reliably distinguish MF from AD. In conclusion, in lesional SC of MF patients, pro‐inflammatory cytokines can be detected. As a diagnostic method, tape stripping of lesional SC cannot discriminate MF skin from AD skin.